Analysis of Rentability Trends of Islamic Commercial Banks in the Covid-19 Pandemic - Alto Wirahadi Kusuma; Ammar Muhajir; Lutfiah Lutfiah; Rafika Rahmawati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The Covid 19 pandemic has caused possible risks to the financial performance of Islamic banking. This study aimed to determine the rentability performance level predictions of Bank Muamalat Indonesia, Bank Mega Syariah, and Bank KB Bukopin Syariah by using the ratio of Return on Assets (ROA) and Return on Equity (ROE) in the pandemic for the period December 2021 to December 2023. The Islamic commercial bank was chosen because its rentability performance showed different trends during the pandemic. The research methods used the quantitative and trend analysis techniques with the least square method. The results have indicated that the rentability performance level of Bank Muamalat Indonesia and Bank KB Bukopin Syariah in terms of the ratio of Return on Assets (ROA) and Return on Equity (ROE) was predicted to decrease from December 2021 to December 2023. Meanwhile, the rentability performance level of Bank Mega Syariah in terms of the ratio of Return on Assets (ROA) and Return on Equity (ROE) was predicted to increase from December 2021 to December 2023. Concerning this, the research is hoped to contribute as reference material for further academic research and as material for consideration in determining policies for Islamic commercial banks.